Foreign exchange risk pricing and equity market segmentation in Africa - Kodongo, Odongo; Ojah, Kalu (Journal of Banking & Finance, 2011)
This work is the first to investigate simultaneously the occurrence of unconditional currency risk pricing and equity market segmentation in Africa’s major stock markets. The multi-factor asset pricing theory provides the theoretical framework for our model. We find strong evidence suggesting that Africa’s equity markets are partially segmented. However, we find insufficient evidence to reject the hypothesis that foreign exchange risk is not unconditionally priced in Africa’s stock markets. This result is robust to alternative foreign exchange rate-adjusted return measures. These findings suggest that international investors can diversify into Africa’s equity markets without worrying about unconditional risks associated with foreign exchange rate fluctuations.